Cover Picture: A Complementary Aggregation Induced Emission Pair for Generating White Light and Four‐Colour (RGB and Near‐IR) Cell Imaging (ChemPhotoChem 3/2017). Issue 3 (8th March 2017) - Sarkar, Samir Kumar; Mukherjee, Sanjoy; Garai, Aditya; Thilagar, Pakkirisamy
Abstract : The Front Cover picture shows how white‐light emission can be generated in aqueous media by doping a BODIPY‐based AIE‐active red emitter inside nanoaggregates of an AIE‐active blue‐emissive dye. More information can be found in the Communication by P. Thilagar and co‐workers onpage 84 in Issue 3, 2017 (DOI:10.1002/cptc.201600032 ).